Associated Factors and Long-Term Prognosis of 24-Hour Worsening of Arterial Patency After Ischemic Stroke. Issue 10 (October 2019) - Marto, João Pedro; Lambrou, Dimitris; Eskandari, Ashraf; Nannoni, Stefania; Strambo, Davide; Saliou, Guillaume; Maeder, Philippe; Sirimarco, Gaia; Michel, Patrik
Abstract : Background and Purpose—: Early arterial recanalization in acute ischemic stroke is strongly associated with better outcomes. However, early worsening of arterial patency was seldom studied. We investigated potential predictors and long-term prognosis of worsening of arterial patency at 24 hours after stroke onset. Methods—: Patients from the Acute Stroke Registry and Analysis of Lausanne registry including admission and 24-hour vascular imaging (computed tomography or magnetic resonance angiography) were included. Worsening of arterial patency was defined as a new occlusion and significant stenosis in any extracranial or intracranial artery, comparing 24 hours with admission imaging. Variables associated with worsening of arterial patency were assessed by stepwise multiple logistic regression. The impact of arterial worsening on 3-month outcome was investigated with an adjusted modified Rankin Scale shift analysis. Results—: Among 2152 included patients, 1387 (64.5%) received intravenous thrombolysis and endovascular treatment, and 65 (3.0%) experienced 24-hour worsening of arterial patency. In multivariable analysis, history of hypertension seemed protective (adjusted odds ratio [aOR], 0.45; 95% CI, 0.27–0.75) while higher admission National Institutes of Health Stroke Scale (aOR, 1.06; 95% CI, 1.02–1.10), intracranial (aOR, 4.78; 95% CI, 2.03–11.25) and extracranial stenosis (aOR, 3.67; 95% CI, 1.95–6.93), and good collaterals (aOR, 3.71; 95% CI, 1.54–8.95) were independent predictors of worsening of arterial patency. Its occurrence was associated with a major unfavorable shift in the distribution of the modified Rankin Scale at 3 months (aOR, 5.97; 95% CI, 3.64–9.79). Conclusions—: Stroke severity and admission vascular imaging findings may help to identify patients at a higher risk of developing worsening of arterial patency at 24 hours. The impact of worsening of arterial patency on long-term outcome warrants better methods to detect and prevent this early complication. Abstract : Supplemental Digital Content is available in the text.